2015
DOI: 10.1080/87565641.2015.1036993
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory for Serial Order Is Dysfunctional in Adults With a History of Developmental Dyscalculia: Evidence From Behavioral and Neuroimaging Data

Abstract: Recent studies suggest that order working memory (WM) may be specifically associated with numerical abilities. This study explored behavioral performance and neural networks associated with verbal WM in adults with a history of developmental dyscalculia (DD). The DD group performed significantly poorer but with the same precision than the control group in order WM tasks and showed a lower activation of the right middle frontal gyrus during the order WM and the alphabetical order judgment tasks. This study sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
1
11
1
Order By: Relevance
“…Regarding the frontal part of the network commonly associated with ordinal processing tasks, although some studies have shown sensitivity to ordinal distance of middle and inferior frontal gyri, this seems to be the case only for ordinal judgment tasks requiring more explicit, controlled judgments (e.g. serial order WM and alphabetic ordinal judgment) but not in numerical ordinal judgment which can rely on the more automatic activation of numerical information (Fulbright et al 2003;Attout et al 2014Attout et al , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the frontal part of the network commonly associated with ordinal processing tasks, although some studies have shown sensitivity to ordinal distance of middle and inferior frontal gyri, this seems to be the case only for ordinal judgment tasks requiring more explicit, controlled judgments (e.g. serial order WM and alphabetic ordinal judgment) but not in numerical ordinal judgment which can rely on the more automatic activation of numerical information (Fulbright et al 2003;Attout et al 2014Attout et al , 2015.…”
Section: Introductionmentioning
confidence: 99%
“…In the memory assessment, there was lower performance of the group with dyscalculia and dyslexia in short-term auditory memory when compared to the non-case group. Studies indicate that this result is expected when these groups are compared to children without difficulties (Attout et al, 2015;Bogaerts et al, 2014). In short-term visual memory, no differences were found among any of the groups.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, deficits in other neuropsychological abilities may secondarily track these major impairments, such as attention, Executive Functions (EF) and memory, both in dyslexia (Bogaerts, Szmalec, Page, & Duyck, 2014;Menghini et al, 2010;Ziegler, Pech-Georgel, Dufau, & Grainger, 2010) and in dyscalculia (Ashkenazi, Rubinsten, & Henik, 2009;Attout, Salmon & Majerus, 2015).…”
mentioning
confidence: 99%
“…In kindergarten children, a longitudinal study (Attout et al ., ) showed that a WM task maximizing maintenance of serial order information predicted calculation abilities one and 2 years later while this was not the case for WM tasks requiring only the maintenance of item information (defined as a temporary activation of phonological and semantic representation of the information). Furthermore, neurodevelopmental studies also revealed a specific deficit to maintain serial order information in WM in individuals presenting with a history of developmental dyscalculia (Attout & Majerus, ; Attout, Salmon, & Majerus, ; De Visscher, Szmalec, Van Der Linden, & Noël, ).…”
Section: Introductionmentioning
confidence: 99%